Retrospective Cohort Observational Study on the Single Best Perforator-Based Pacman Flap in the Reconstruction of Stage IV Sacral Region Pressure Ulcers - T. M. Balakrishnan; Basker Kanagaraj Mariappan; J. Jaganmohan (Indian Journal of Plastic Surgery)
Introduction Single best perforator-based Pacman flap (SBPBPF) fortifies the advancement and transposition flap biogeometry principles with robust blood supply of perforator flaps to provide cover for the sacral pressure sore of any dimension. This article describes the biogeometry and technique of raising the SBPBPF. Aim To assess the outcomes of reconstruction of stage IV sacral pressure sore using the SBPBPF. Materials and Methods A preliminary cadaver study was done in 24 gluteal specimens in fresh cadavers to determine the anatomical details of perforators of the perisacral region. From 2015 to 2017, 42 myelopathic patients (40 males and 2 females; quadriparetic n = 2 and paraplegic/paraparetic n = 40) underwent SBPBPF reconstruction of stage IV sacral pressure sore. Their documents were analyzed in this retrospective study. All were followed-up for an average period of 12.5 months. Results Cadaver study revealed significant perforators arising from seven different source vessels in the perisacral region. In the clinical study, average size of the paddle harvested was 168 cm2 on a single best perforator. On an average, the size of the single best perforator harvested with the flap was 1.5 mm. None had early failures of flaps. Thirty-nine patients had well-settled flaps at the end of follow-up period except three (7%) who developed late recurrence due to loss of compliance with offloading instructions. Two experienced mild collections (flap complication rate was 4.76%) in the immediate postoperative period that healed uneventfully. The overall complication rate was 11.9%. Conclusion SBPBPF is an excellent addendum to reconstructive tool for stage IV sacral pressure sores.